The Cultural Problems about the Adaptation of Manggarai Students in Malang City - Gultom, Andri Fransiskus (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2024)
This research is motivated by the cultural complexity between Manggarai students and Java students in Malang city, Indonesia. There are misunderstandings due to the meeting of two different cultures. The research purpose is to find out the adaptation problems of Manggarai students in Malang city. The research method is qualitative with an ethnographic approach, namely emic. The data collection techniques are observation, interview and documentation. The analysis technique uses interpretation with a cultural paradigm. The results showed that the cultural problem of adaptation in the ethnographic point of view is the difficulty of adapting between students from Manggarai (migrants) and students from Java (host culture). The main reason for the difficulty in adapting starts from the language, the situation of feeling like a foreigner so that they feel culture shock with the new culture. Consequences of adaptation problems: limited communication between the two parties, the problem of occurring situations that are not familiar and easily offended due to misunderstanding and suspicion in the use of language. Ethnographic analysis helps adaptation problems through cultural trajectories from the immigrant side by being humble to learn conversations in everyday Javanese. The trajectory is carried out communally with initiatives from regional organizations (Lembor Malang Big Family Association or IKBLM) to build meeting points and familiarity with Javanese students. Research recommendations, different cultures can be crossed with cultural ideas and actions to accept differences starting from migrants and facilitated by decision-making parties.